2016
DOI: 10.1024/1012-5302/a000475
|View full text |Cite
|
Sign up to set email alerts
|

Erleben und Unterstützungsbedarf von Eltern hospitalisierter Kinder mit Mehrfachbehinderung

Abstract: Zusammenfassung Experiences and support needs of parents of hospitalised children with multiple disabilities: A qualitative study Abstract:Background: The hospitalisation of a multiple disabled child is stressful for parents because they continue to carry out demanding care procedures in hospital. Yet, systematic knowledge of the parental experience and of their support needs is missing. Question: How do parents experience the hospitalisation, and which support needs do they identify for this period? Methods: … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
2

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 14 publications
0
2
0
Order By: Relevance
“…In order to systematically explore the parents' specific experiences and support needs, we began by conducting a systematic review (Seliner et al, 2015) followed by a qualitative and a cross-sequential study involving parents of hospitalized children with PIMDs at the children's hospital in question (Seliner et al, 2016a(Seliner et al, , 2016b. Both studies showed a need for quality improvement at all levels.…”
Section: Theoretical Base Of the Intervention Development (Phase 1)mentioning
confidence: 99%
See 1 more Smart Citation
“…In order to systematically explore the parents' specific experiences and support needs, we began by conducting a systematic review (Seliner et al, 2015) followed by a qualitative and a cross-sequential study involving parents of hospitalized children with PIMDs at the children's hospital in question (Seliner et al, 2016a(Seliner et al, , 2016b. Both studies showed a need for quality improvement at all levels.…”
Section: Theoretical Base Of the Intervention Development (Phase 1)mentioning
confidence: 99%
“…This challenge for parents intensifies when the child's disabilities are severe (Ausserhofer, Mantovan, Pirhofer, Huber, & Them, ). In particular, parents worry about their child's well‐being and feel responsible for safeguarding the child's welfare (Oulton & Heyman, ; Seliner, Latal, & Spirig, ). Family‐centered care (FCC) is essential for these families during hospitalization, as the concept has been shown to positively affect the child and the family through support of the family system (Jansen, van der Putten, Post, & Vlaskamp, ).…”
Section: Introductionmentioning
confidence: 99%